Differences in post-traumatic growth: Individual quarantine, COVID-19 duration and gender - Cohen-Louck, Keren (Frontiers in Psychology, 2022)
Objective: This study focuses on positive effects of the COVID-19 pandemic and aims to identify associations between gender, individual quarantine and duration of the COVID-19 (short- medium- and long-term pandemic), and posttraumatic growth (PTG). Method: The data was collected via an online survey in Israel, and included 1301 participants, 543 participants experienced short-term pandemics, 428 participants experienced medium-term pandemics and 330 participants experienced long-term pandemics. Most of the participants were female (73.6%), ranging from 18 to 89 years-old. The participants answered questions about their demographic background, individual quarantine experiences and ranked their PTG level. Results: The results indicate a significant main effect of gender and pandemic duration (short-, medium- and long-term pandemic). Women reported higher PTG levels than men, and participants experiencing short-term pandemic reported significantly lower PTG levels than participants experiencing medium- or long-term pandemic. There was also a significant interaction between gender and pandemic duration regarding PTG and a significant interaction in PTG by gender, pandemic duration and individual quarantine. Conclusions: The discussion addresses the findings in the context of traditional gender roles and gender differences in finding meaning and worth in home confinement situations.